Cover Image, Volume 35, Issue 5. (6th June 2019) - Thoms, Martin; Sheldon, Fran
Abstract : The cover image is based on the Special Issue Paper LARGE RIVERS AS COMPLEX ADAPTIVE ECOSYSTEMS by Martin Thoms and Fran Sheldon, https://doi.org/10.1002/rra.3448 . Cover image © David Mussred.